130-[5.(9-x)+43]=47
5.(9-x)+43=130-47
5.(9-x)+43=83
5.(9-x)=83-43
5.(9-x)=40
9-x=40:5
9-x=8
x=9-8
x=1
\(130-\left[5\times\left(9-x\right)+43\right]=47\)
\(\Rightarrow\left[5\times\left(9-x\right)+43\right]=130-47\)
\(\Rightarrow\left[5\times\left(9-x\right)\right]=83\)
\(\Rightarrow\left(9-x\right)=83\div5\)
\(\Rightarrow\left(9-x\right)=\frac{83}{5}\)
\(\Rightarrow x=9-\frac{83}{5}\)
\(\Rightarrow x=-\frac{38}{5}\)
Mình nhầm :
\(130-\left[5\times\left(9-x\right)+43\right]=47\)
\(\Rightarrow\left[5\times\left(9-x\right)+43\right]=130-47\)
\(\Rightarrow\left[5\times\left(9-x\right)+43\right]=83\)
\(\Rightarrow5\times\left(9-x\right)=83-43\)
\(\Rightarrow5\times\left(9-x\right)=40\)
\(\Rightarrow\left(9-x\right)=40\div5\)
\(\Rightarrow\left(9-x\right)=8\)
\(\Rightarrow x=9-8\)
\(\Rightarrow x=1\)